PENGGUNAAN ALAT MUSIK PIANIKA DALAM PEMBELAJARAN SENI BUDAYA DI SMP NEGERI 3 PAINAN - Gian Jenifer; Syeilendra Syeilendra; Yensharti Yensharti (SENDRATASIK UNP, 2018)
Abstract This article aims to describe the use of musical instruments in Country Junior High School 3 pianika Painan. This research uses qualitative descriptive method. The object of research in class VIII-3. Engineering data collection done by observation, interviews, and the study of the literature. The data were analyzed using data processing techniques consisting of primary data and data skunder. The data is then classified, described, interpreted and then compiled in systematics and then summed up. The research began by observing the activities of the process of learning the art of music pianika happens in class VIII. 3. Starting from studying the syllabus and the RPP have been designed by the art and culture of SMP N 3 Painan. From the results of observation of the process that performed the teacher in class VIII. 3 the research results obtained are as follows: that the exercise of learning music pianika already well underway in accordance with the draft syllabus and RPP made teachers. But in the process of its implementation, there is also the difficulty of some of the students when playing tones of songs that does not correspond to the value of the duration or its rhythm so that songs can not be played perfectly. To resolve this issue of teacher gives motivation by means of assigning students to exercise more at home. By doing exercises that repeatedly found better results where students can eventually play songs with good tempo and rhythm.Keywords: The Use Of Musical Instruments, Pianika, Arts And CultureAbstract This article aims to describe the use of musical instruments in Country Junior High School 3 pianika Painan. This research uses qualitative descriptive method. The object of research in class VIII-3. Engineering data collection done by observation, interviews, and the study of the literature. The data were analyzed using data processing techniques consisting of primary data and data skunder. The data is then classified, described, interpreted and then compiled in systematics and then summed up. The research began by observing the activities of the process of learning the art of music pianika happens in class VIII. 3. Starting from studying the syllabus and the RPP have been designed by the art and culture of SMP N 3 Painan. From the results of observation of the process that performed the teacher in class VIII. 3 the research results obtained are as follows: that the exercise of learning music pianika already well underway in accordance with the draft syllabus and RPP made teachers. But in the process of its implementation, there is also the difficulty of some of the students when playing tones of songs that does not correspond to the value of the duration or its rhythm so that songs can not be played perfectly. To resolve this issue of teacher gives motivation by means of assigning students to exercise more at home. By doing exercises that repeatedly found better results where students can eventually play songs with good tempo and rhythm.  64 Keywords: The Use Of Musical Instruments, Pianika, Arts And Culture